Experimental Study on Autogenous and Drying Shrinkage of Steel Fiber Reinforced Lightweight-Aggregate Concrete - Shunbo Zhao; Changyong Li; Mingshuang Zhao; Xiaoyan Zhang (Advances in Materials Science and Engineering)
Steel fiber reinforced lightweight-aggregate concrete (SFRLAC) has many advantages applied in structural engineering. In this paper, the autogenous shrinkage and drying shrinkage of SFRLAC for up to 270 days were measured, considering the effects of types of coarse and fine aggregates with the changes of water-to-binder ratio and volume fraction of steel fiber, respectively. The properties of mix workability, apparent density, and compressive strength of SFRLAC were also reported and discussed in relation to above factors. Test results show that the development of autogenous and drying shrinkage of SFRLAC was fast within 28 days and tended to be steady after 90 days. The development of autogenous shrinkage of SFRLAC reduced with the increasing water-to-binder ratio and by using the expanded shale with higher soundness and good water absorption, especially at early age within 28 days; the later drying shrinkage was reduced and the development of drying shrinkage was slowed down with the increasing volume fraction of steel fiber obviously; manufactured sand led to less autogenous shrinkage but greater drying shrinkage than fine lightweight aggregate in SFRLAC. The regularities of autogenous shrinkage and drying shrinkage of SFRLAC expressed as the series of hyperbola are analyzed.